The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/jvp.12208
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and distribution of voriconazole in body fluids of dogs after repeated oral dosing

Abstract: The goal of this project was to determine the pharmacokinetics of voriconazole and its concentration in cerebrospinal fluid (CSF), aqueous humor, and synovial fluid in five healthy dogs following once daily oral dose of 6 mg/kg for 2 weeks. Body fluid and plasma drug concentrations were determined by high-performance liquid chromatography (HPLC). Mild to moderate gastrointestinal adverse effects were seen. The mean AUC0-24 : minimum inhibitory concentration (MIC) ratio was 15.23 for a chosen MIC of 1 μg/mL, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
(55 reference statements)
0
8
0
3
Order By: Relevance
“…2 There have been only a few reports describing the transfer of VRCZ to cerebrospinal fluid (CSF). [3][4][5] Here, we report analysis of VRCZ concentrations in CSF during prophylactic use in pediatric patients with acute myelogenous leukemia (AML).…”
mentioning
confidence: 99%
“…2 There have been only a few reports describing the transfer of VRCZ to cerebrospinal fluid (CSF). [3][4][5] Here, we report analysis of VRCZ concentrations in CSF during prophylactic use in pediatric patients with acute myelogenous leukemia (AML).…”
mentioning
confidence: 99%
“…Previous studies have similarly reported rapid increases in plasma concentrations of this drug after oral administration in horses, human beings, dogs, and cats. 20,33,35,36 This has been attributed to the high solubility and permeability of voriconazole. 33 It was confirmed that voriconazole was absorbed rapidly in healthy horses after a single oral administration in this study.…”
Section: Discussionmentioning
confidence: 99%
“…(iv) Despite its long history of usage, much is still unknown concerning the pharmacokinetics of amphotericin B, especially in the veterinary treatment (Davis, Papich, & Heit, 2009). Moreover, data on the pharmacokinetics of amphotericin B‐containing liposomes are scarce in the literature and are mostly obtained from beagle dogs (Fukui et al., ; Serrano et al., ), which have generally different pharmacokinetics from the other breeds (Lemetayer, Dowling, Taylor, & Papich, ). The present study was therefore conducted with mixed breed dogs instead of beagle dogs, to represent the pharmacokinetics of general dog population more precisely.…”
Section: Discussionmentioning
confidence: 99%